ChemInform Abstract: Exploring the Reactivity of N‐Alkynylated Sulfoximines: [2 + 2]‐Cycloadditions. Issue 11 (18th March 2014) - Pirwerdjan, Ramona; Priebbenow, Daniel L.; Becker, Peter; Lamers, Philip; Bolm, Carsten
Abstract The [2 + 2]‐cycloaddition of N‐alkynyl substituted sulfoximes (I) with in situ generated ketenes affords a series of sulfoximidoyl functionalized cyclobutenones.